The relevance of computer subjects taken by accountancy graduates of UPV in their line of profession - Aguirre, Jesil; Arenga, Archie; Asong, Olive Grace; Gatusang, Therese; Grasparil, Lyra; Navarra, Ines; Vego, Cheryl
Executive summary - This statistical study was conducted in order to determine the relevance of computer subjects taken by accountancy gradutes of UPV in their line of profession. The professions considered were Accountant, Auditor, Bookkeeper, Cashier/Teller, and Researcher. Data were taken from the population of accounting graduates in UPV from years 1995-1997. Information was gathered using personal interviews and questionnaires. The results were tabulated and analyzed using the mean of weighted rates and one-way classification variance analysis. The results of the study revealed that computer subjects are relevant to the professions, however their significance is relative to the occupation. The underlying reason for this is diversity of the work of a profession requires different set of computer knowledge and the level of complexity the computer system being used by the employers also affect the usefulness of the computer subjects taken.